SARS-COV-2: USPON I PAD HRVATSKOG SCENARIJA. ETNOGRAFIJA KORONAPOLITIKA U HRVATSKOM UPRAVLJANJU PANDEMIJSKOM KRIZOM - Prica, Ines (Bulletin of the Institute of Ethnography SASA, 2021)
The oscillations in the Croatian scenario of the struggle with the pandemic are followed by the considerable rearrangements of the key social actors. The initial success in the controle of the disease, as well as goverment measures for the rescue of national economy (recognized as the return of social state), have led to the unprecedentent public suppport and hope in the renowal of the disturbed social cohesion. The optimism was projected in the unexpected cognitive collectivity awaken by trust in the credible and expert management of the crisis, clear of political manipulations. Nevertheless, the divergence in both political and professional judgements of the coming changes of epidemiological measures, aimed to balance the public health and the social-economic risks, have led to the unexpected realignments of the social-critical stances, especially concerning the cultural understanding of labour economic relations, marked by the conflict of the public and private sector.